Validity and Asymmetry of Okun’s Law: Evidence from Asian Economies - Rasul, Farhat; Asghar, Nabila; Rehman, Hafeez ur (iRASD Journal of Economics, 2021)
This study investigates the validity and asymmetry of output-unemployment relationship for three groups: high income, upper middle income and lower middle income Asian Economies over the period of 1980-2018. This study investigates whether the behavior of labor markets is rigid or flexible in these economies over the sample period. By using the Hodrick and Prescott filter, the study finds a statistically significant relationship between cyclical output and cyclical unemployment; hence provides the evidence of the existence of Okun’s Law with more sensitive results for the lower middle economies as compared to other groups of countries. The study also discovers the evidence of asymmetric relationship of output-unemployment during the recessionary and expansionary period of economic growth. Although the value of coefficient varies due to asymmetry but the variation is found to be small across the three groups of the countries. The study concludes that sample economies have rigid labor markets indicating the persistence of structural unemployment.